The People's Economy Approach in the Management of Natural Resources by State-Owned Enterprises in Indonesia - Tina Amelia (Dinasti Research, 2024)
The management of natural resources in Indonesia is constitutionally mandated to follow a people's economy approach, prioritizing public welfare. However, there has been a significant deviation from this principle, with the State-Owned Enterprises Law (UU BUMN) promoting privatization and commercialization, rather than the intended economic model. This reveals a critical gap between constitutional ideals and actual policy implementation. This paper aims to address this gap by examining the inconsistency between the constitution and current SOE practices, particularly in natural resource management. Utilizing a normative juridical research methodology, combining statutory and conceptual approaches, this study investigates how SOEs have increasingly focused on profit maximization, often at the expense of sustainable development and local community welfare. Key findings highlight a fundamental misalignment between the constitutional mandate and the operational goals of SOEs, which now prioritize excessive exploitation for financial gains. The implications of this research suggest an urgent need to reform SOE policies, steering them towards sustainable practices that align with the people’s economy model and the constitutional goal of achieving the greatest prosperity for all citizens. Reorienting SOE management to balance profit and sustainability is essential for protecting both natural resources and the long-term interests of local communities.